1994
DOI: 10.1177/1050651994008001003
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Gender Studies to Professional Communication Research

Abstract: This article reviews selected gender scholarship that informs the study of professional communication as well as some recent articles on professional communication that make use of gender studies. The article also suggests future research directions that include a merger of gender and professional communication scholarship. Topics covered include gender and communication and gender identity, along with gender and writing, reading, speaking language choice, visual communication, collaboration, content analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The authors finding in another way round disagreed with the present finding as they argue that female managers tend to use interpersonal, compromising, co-operative, collaborative, avoiding, pro-social, and communicative approaches in the course of managing industrial conflict. While male managers often utilized more aggressive, competitive, confronting, assertive, pro-task and coercive approaches more often than the female managers, even when collective bargaining strategy is being adopted (Gibbs and Lach, 1994;Lay, 1994;Akintayo, 2004;Ajaja, 2004;Adeyemo, 2005). Hypothesis three predicted that there is no difference between male and female managers' conflict resolution effectiveness.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors finding in another way round disagreed with the present finding as they argue that female managers tend to use interpersonal, compromising, co-operative, collaborative, avoiding, pro-social, and communicative approaches in the course of managing industrial conflict. While male managers often utilized more aggressive, competitive, confronting, assertive, pro-task and coercive approaches more often than the female managers, even when collective bargaining strategy is being adopted (Gibbs and Lach, 1994;Lay, 1994;Akintayo, 2004;Ajaja, 2004;Adeyemo, 2005). Hypothesis three predicted that there is no difference between male and female managers' conflict resolution effectiveness.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Considering the conflict management style, researchers have indicated that female supervisors tend to use interpersonal, compromising, collaborative, accommodating, integrating, co-operative, avoiding, pro-social and communicative methods. In contrast, there is evidence that male managers tend to use more aggressive competitive, confronting, assertive, pro-task and coercive strategies more often and faster than female managers (Gibbs & Lach, 1994;Lay, 1994;Sorenson &Hawkins, 1995;Conrad, 1991;Akintayo, 2004;Ajaja, 2004;Adeyemo, 2005). Babajide (2000) noted that authoritarian style is prevalent among female managers and a democratic style is manifested by male managers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have suggested that a combination of masculinity and femininity provides the maximum benefits rather than being stereotyped as masculine or feminine (Guastello & Guastello 2003). From a manager's perspective, being androgynous helps them to become effective at work (Sargeant, 1981) and perceived more positively by their subordinates (Jurma & Powell 1994;Lay, 1994).…”
Section: Gender Role Identity (Gri) and Emotional Intelligencementioning
confidence: 99%
“…Feminist technical communication scholars have also argued for extending the concerns of professional communication to public life and social projects. Among others, Lay ( 1989) has surveyed the value of gender studies for professional communication, and LaDuc and Goldrick-Jones (1994) have articulated how feminist contributions can foreground ethical concerns and help teachers and practitioners understand the ways power is implicated in technical communication practice.…”
Section: Professional Communication and Social Actionmentioning
confidence: 99%